Formation of dislocations via misfit strain across interfaces in epitaxial BaTiO3 and SrIrO3 heterostructures. (28th May 2021) - Saghayezhian, M; Wang, Z; Howe, D; Siwakoti, P; Plummer, E W; Zhu, Y; Zhang, Jiandi
Abstract: Dislocations often occur in thin films with large misfit strain as a result of strain energy accumulation and can drastically change the film properties. Here the structure and dislocations in oxide heterostructures with large misfit strain are investigated on atomic scale. When grown on SrTiO3 (001), the dislocations in both the monolithic BaTiO3 thin film and its superlattices with SrIrO3 appear above a critical thickness around 6 nm. The edge component of the dislocations is seen in both cases with the Burgers vector of a ⟨100⟩. However, compared to monolithic BaTiO3, the dislocation density is slightly lower in BaTiO3 /SrIrO3 superlattices. In the superlattice, when considering the SrTiO3 lattice constant as the reference, BaTiO3 has a larger misfit strain comparing with SrIrO3 . It is found that in both cases, the formation of dislocation is only affected by the critical thickness of the film with larger lattice misfit (BaTiO3 ), regardless of the existence of a strong octahedral tilt/rotation mismatch at BaTiO3 /SrIrO3 interface. Our findings suggest that it is possible to control the position of dislocations, an important step toward defect engineering.